A literature review of the history and evolution of corporate social responsibility - Mauricio Andrés Latapí Agudelo; Lára Jóhannsdóttir; Brynhildur Davídsdóttir (International Journal of Corporate Social Responsibility (JCSR), 2019)
There is a long and varied history associated with the evolution of the concept of Corporate Social Responsibility (CSR). However, a historical review is missing in the academic literature that portrays the evolution of the academic understanding of the concept alongside with the public and international events that influenced the social expectations with regards to corporate behavior. The aim of this paper is to provide a distinctive historical perspective on the evolution of CSR as a conceptual paradigm by reviewing the most relevant factors that have shaped its understanding and definition, such as academic contributions, international policies and significant social and political events. To do so, the method used is a comprehensive literature review that explores the most relevant academic contributions and public events that have influenced the evolutionary process of CSR and how they have done so. The findings show that the understanding of corporate responsibility has evolved from being limited to the generation of profit to include a broader set of responsibilities to the latest belief that the main responsibility of companies should be the generation of shared value. The findings also indicate that as social expectations of corporate behavior changed, so did the concept of Corporate Social Responsibility. The findings suggest that CSR continues to be relevant within the academic literature and can be expected to remain part of the business vocabulary at least in the short term and as a result, the authors present a plausible future for CSR that takes into consideration its historical evolution. Finally, this paper gives way for future academic research to explore how CSR can help address the latest social expectations of generating shared value as a main business objective, which in turn may have practical implications if CSR is implemented with this in mind.
Keywords: 650; Corporate social responsibility; CSR evolution; CSR history; Sustainable development; Generation of shared value; Social responsibility; Corporate behavior